ANALISIS BEBAN KERJA KARYAWAN DEPARTEMENT PRODUKSI DENGAN METODE FULL TIME EQUIVALENT (FTE) DI PT XYZ - Elistia Octaviani; Cattleya Prameswari Anissa Islami, Mega (Sekolah Tinggi Teknologi Kedirgantaraan, 2025)
In the era of globalization and increasingly fierce industrial competition, operational efficiency has become a key to corporate success. PT XYZ, as a manufacturing company in the packaging production sector, faces challenges in optimizing human resource utilization, particularly in the production department. This study aims to analyze employee workload in the production department using the Full Time Equivalent (FTE) method. The identified issue is the variation in workload levels between production administrative staff and machine operators, which can affect productivity and employee well-being. The FTE method is applied to measure workload based on the frequency and duration of activities. The results indicate that production administrative staff have an FTE value of 1.55, indicating a workload that exceeds the ideal capacity, posing risks of fatigue and decreased work quality. Conversely, machine operators AMS, LT, and MTB are in an optimal condition with FTE values of 0.91 and 0.97, respectively. However, operators on the OMSO machine show a light workload of 0.75, while operators on the BONMAC TCL and CER machines experience overload with FTE values of 1.65. Based on these findings, it is recommended to increase the number of production administrative staff to two and the number of operators on the BONMAC TCL and CER machines to two as well, to prevent excessive workloads. Future research is suggested to explore other factors affecting workload and conduct a more in-depth analysis of employee well-being's impact on productivity. Thus, the application of the FTE method can be optimized to enhance operational efficiency within the company.